International Journal of Maritime Engineering 2018
DOI: 10.3940/rina.ijme.2018.a1.444
|View full text |Cite
|
Sign up to set email alerts
|

An ICOR Approach Towards Ship Maintenance Software Development

Abstract: Ship maintenance is one of the key processes to improve system performance and reliability onboard. Maintenance onboard ships is required to be performed in a planned manner because safe and efficient operation of a ship is very much depending on equipment reliability in operational level. A planned maintenance system (PMS), mainly supported with software, is established to monitor the maintenance implementations on board ships. This study aims to assess the effectiveness of onboard maintenance and limited wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…The PMS is a system that is used for planning and monitoring machinery equipment overhauling and maintenance, based on manufacturers and class recommended time intervals. 32 It is also used as a database for recording service work orders as well as maintenance and failure data. 32 During the preparatory step, the failure rates, failure modes and failure modes probability for each system component and their distribution are also identified based on this information and the relevant literature.…”
Section: Methodology Overview and Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…The PMS is a system that is used for planning and monitoring machinery equipment overhauling and maintenance, based on manufacturers and class recommended time intervals. 32 It is also used as a database for recording service work orders as well as maintenance and failure data. 32 During the preparatory step, the failure rates, failure modes and failure modes probability for each system component and their distribution are also identified based on this information and the relevant literature.…”
Section: Methodology Overview and Rationalementioning
confidence: 99%
“…32 It is also used as a database for recording service work orders as well as maintenance and failure data. 32 During the preparatory step, the failure rates, failure modes and failure modes probability for each system component and their distribution are also identified based on this information and the relevant literature. 33,34 More specifically, adhering to exponential failure distribution, the failure rates and Mean Time to Repair (MTTR) of the machinery components are derived by calculating the quotient of the number of failures divided by the overall running hours.…”
Section: Methodology Overview and Rationalementioning
confidence: 99%
“…В цілому, аналіз останніх досліджень і публікацій вказує на важливість впровадження інформаційних систем моніторингу ефективності технічного обслуговування суден. Важливими постають питання: системного технічного обслуговування, що орієнтоване на надійність (SRCM), яке ефективно підвищує надійність і безпеку повністю електричних суден шляхом визначення оптимальних завдань технічного обслуговування і використання методів управління ризиками, таких як аналіз рівнів захисту (LOPA) [1]; оцінювання ефективності технічного обслуговування суден за допомогою підходу до аналізу процесів, заснованого на вхідних, контрольних, вихідних даних і ресурсах (ICOR) [2]; оцінювання ефективності технічного обслуговування суден шляхом застосування моделі на основі Марківського аналізу для оцінки надійності кожної підсистеми, а потім розгляд шляхів підвищення надійності та вимірювання економічних переваг [3]; автоматизації оцінки стану танків і конструкцій вантажних суден за допомогою бездротової технології, яка значно скорочує час і зусилля, максимізуючи ефективність, економічність і надійність суден [4]. Метод оцінки життєвого циклу збільшує значення операційного показника енергоефективності (EEOI) в реальному часі, особливо при менших обертах двигуна і меншій осадці судна, оцінюючи ефективність технічного обслуговування судна [5].…”
Section: вступunclassified
“…There are also many studies can be found in the maritime literature on maintenance planning at shipboard operations. For instance, Bayer et al 16 conducted a study toward improving the planning process, ensuring workload balance to improve functionality, performing intelligent programming, and integrating safe working modules into existing planned maintenance software. Likewise, Tan et al 17 have intended an algorithm to integrate with condition monitoring system in order to decrease complexity of marine machinery systems.…”
Section: Introductionmentioning
confidence: 99%